Power and Choice : - Shively, W. Phillips (McGraw-Hill, 2003)
The extensively revised eleventh edition of W. Phillips Shively’s Power & Choice: An Introduction to Political Science maintains the author’s goal since the text’s inception: to provide a general, comparative introduction to the major concepts and themes of political science by engaging students with concrete examples of analysis without overwhelming them with excessive detail.